Conviviality, family arrangements and gender relations in Buenos Aires during the Covid-19 pandemic - Piovani, Juan Ignacio (2024)
This article presents results for the Metropolitan Area of Buenos Aires, Argentina, from a survey on the effects of the Covid-19 pandemic on households, in relation to the distribution of domestic work and the use of spaces for teleworking. The study shows the persistence of gender inequalities in the distribution of domestic and care tasks, which even intensified during the pandemic, increasing the burden on women.